English medium instruction: Policies for constraining potential language use in the classroom and recruiting instructors - Seniye Vural; Zeynep Ölçü Dinçer (Ömer Gökhan Ulum, 2022)
English medium instruction (EMI), has posed benefits and challenges in Higher Education Institutions (HEIs). Especially in the contexts where English is used as a foreign language, EMI universities may face two significant problems: 1) finding instructors meeting both academic and English proficiency requirements, 2) constraining potential language use in the classrooms where the majority of the students and the instructor share the same mother tongue. This study aims to unearth the policies employed by the three state EMI universities to handle these problems. Content analysis is used for the data consisting of documents and administrators' responses to an online open-ended questionnaire. The findings reveal that the primary supply for instructor demand is the local academics with EMI background and academic experiences abroad. There is no policy that directly constrains the classroom language to English, but universities make use of some indirect policy mechanisms such as including language of instruction in course evaluation forms and increasing the number of international students.